1999
DOI: 10.1097/00003246-199904000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Stress doses of hydrocortisone reverse hyperdynamic septic shock

Abstract: Infusion of stress doses of hydrocortisone reduced the time to cessation of vasopressor therapy in human septic shock. This was associated with a trend to earlier resolution of sepsis-induced organ dysfunctions. Overall shock reversal and mortality were not significantly different between the groups in this low-sized single-center study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 791 publications
(112 citation statements)
references
References 45 publications
5
102
0
5
Order By: Relevance
“…We searched for references published in 2004 or later, when the standardized care for sepsis was introduced by SSCG 2004 after being defined in 1992 as a systemic inflammatory response syndrome (SIRS) accompanying infection, with the keywords “septic shock” and “low‐dose steroid,” and identified eight RCTs (Bollaert et al .,162 Briegel et al .,163 Chawla et al .,164 Annane et al .,165 Oppert et al .,166 Mussack et al .,167 Sprung et al .,156 and Arabi168). As these eight studies were all included in the meta‐analysis by Wang et al .,160 we initially decided to use it for this CQ.…”
Section: Cq8: Corticosteroid Therapy For Septic Shockmentioning
confidence: 99%
“…We searched for references published in 2004 or later, when the standardized care for sepsis was introduced by SSCG 2004 after being defined in 1992 as a systemic inflammatory response syndrome (SIRS) accompanying infection, with the keywords “septic shock” and “low‐dose steroid,” and identified eight RCTs (Bollaert et al .,162 Briegel et al .,163 Chawla et al .,164 Annane et al .,165 Oppert et al .,166 Mussack et al .,167 Sprung et al .,156 and Arabi168). As these eight studies were all included in the meta‐analysis by Wang et al .,160 we initially decided to use it for this CQ.…”
Section: Cq8: Corticosteroid Therapy For Septic Shockmentioning
confidence: 99%
“…The benefit of hydrocortisone in patients with septic shock has been evaluated in 6 randomized control trials [34,45,48,49,50,51]. A meta-analysis of these trials demonstrates greater shock reversal on day 7 with hydrocortisone, but no benefit in terms of mortality [9].…”
Section: Managementmentioning
confidence: 99%
“…Recent work demonstrated that HE is the interplay between ammonia, inflammatory responses and autoregulation of cerebral hemodynamics [40]. 84 such cirrhotics were studied by Briegel et al [41]. The presence and severity of minimal HE were independent of severity of liver disease and ammonia concentration, but markers of inflammation were significantly higher in those with minimal HE compared with those without.…”
Section: Role Of Cytokines In Liver Complicationsmentioning
confidence: 99%